Marital Satisfaction Trends in Hong Kong Between 2002 and 2012. Issue 5 (3rd July 2016) - Zhang, Huiping; Fan, Susan; Yip, Paul
Abstract : Macrosocial changes may generate influences on marital quality. This study used data from the 2002–2012 Knowledge, Attitude, and Practice surveys conducted by the Family Planning Association of Hong Kong to track the trends of marital satisfaction of both husbands and wives over a 10-year period in Hong Kong, with associated factors. Results indicated that 85% of the husbands and around 80% of the wives reported that they were satisfied with their marital relationships, and no significant changes in general were observed for them between 2002 and 2012 except for some subgroups. Husbands aged 45–49 years, in employment and whose monthly household income between 25, 000 HKD and 39, 999 HKD, reported marital satisfaction decreased over the past 10 years and wives with primary education or below also reported a decreasing trend during this period. Education and family income had positive influences on the husbands' and wives' marital satisfaction, and husbands were more likely to be sensitive to the unemployment. Less than one-third of couples needed professional counseling on family-related issues, and couple conflicts and work–family conflicts were the urgent needs that should be given priority in delivering services. The implications of this study are discussed in the Chinese context of Hong Kong.